NIMG-69. CHANGES IN SIGNAL INTENSITY RATIOS OF GLOBUS PALLIDUS AND DENTATE NUCLEUS ON UNENHANCED T1-WEIGHTED IMAGES AFTER MULTIPLE ADMINISTRATIONS OF MACROCYCLIC GADOLINIUM-BASED CONTRAST AGENTS IN BRAIN TUMOR PATIENTS. (5th November 2018) - Rozenblatt, Shira; Luckman, Judith; Yust-Katz, Shlomit; Siegal, Tali
Abstract: INTRODUCTION: Gadolinium-based contrast agents (GBCAs) are routinely used in MRI studies performed for evaluation of brain tumors. Recent studies have demonstrated, progressively increased signal intensity in the globus pallidus (GP) and dentate nucleus (DN) on T1-weighted brain images obtained in patients undergoing repeated MR studies. Linear GBCAs result in more retention and longer time of retention than macrocyclic GBCAs. The aim of this study is to evaluate changes in signal intensity ratios of the GP and the DN on unenhanced T1-weighted images after multiple administrations of macrocyclic GBCAs in brain tumor patients. METHODS: The study included 37 patients with primary brain tumors who had more than 3 MRI evaluations (range: 4–10 studies). Ten of them (27%) have not receive radiation therapy. Patients were divided into two groups: Group 1 included 24 patients who had Gadoterate meglumine (Dotarem®) enhanced MRI and group 2 included 13 patients who had Gadobutrol (Gadavist®) enhanced MRI. Median age of group 1 patients was 46 (24–69) years and of group 2 it was 56 (32–67). Two radiologists conducted a quantitative analysis of unenhanced T1-weighted images by using region of interest measurements. The difference in mean GP-to-thalamus (GPÞ) signal intensity ratio, DN-to-middle cerebellar peduncle (DN\MCP) signal intensity ratio between the first and last examinations for each patient were calculated. RESULTS: In both groups GP Þ Ratio difference was greater than 0 (Gadavist 0.08 ± 0.06, Dotarem 0.02 ± 0.08 [P=0.035]) following multiple MRI examinations. There was no significant change in DN\MCP ratio in both groups (Gadavist 0.02 ± 0.07, Dotarem -0.01 ± 0.08 [P=0.230]). CONCLUSION: A significant increased GP\Thal ratio is associated with multiple administrations of both macrocyclic agents, but to a greater extent with administration of Gadavist possibly reflecting the difference in elimination and stability of both contrast agents. Further studies are needed to identify clinical implications, if any, of these findings.